Hur kan Östersjöns salinitet påverkas av ett förändrat klimat? - Lindén, Jonathan (SLU/Dept. of Energy and Technology, 2019)
The Baltic Sea is one of the largest brackish seas in the world, with a characteristic salinity gradient from its northernmost point southward towards the Danish Straits. This gradient is caused by a high freshwater input from its surrounding catchment areas. With a low evaporation rate, this leads to an abundance of freshwater which is forced to flow from the Baltic Sea to the North Sea through the Danish Straits.